Effects of lean and six sigma initiatives on continuous quality improvement of the accredited hospitals - Ahmed, Selim; Islam, Rafikul; Ashrafi, Dewan Mehrab; Alqasmi, Ibrahim; Choudhury, Musfiq Mannan; Rahman, Mahfuzur; Dhar, Babul Kumar (Taylor and Francis Ltd., 2023)
The main purpose of this study is to investigate the role of Lean and Six Sigma initiatives on continuous quality improvement in the Malaysian Society for Quality in Health (MSQH) accredited hospitals. In particular, it investigates the relationship between top management support and teamwork. It also examines the influence of teamwork on Lean and Six Sigma initiatives. In this study, 450 survey questionnaires were distributed to twelve MSQH accredited hospitals’ staff using the Stratified Random Sampling method and received 251 useable responses constituting a 55.78 per cent response rate. The reliability and validity of the research variables were tested based on internal consistency, construct validity and discriminant validity by applying the SmartPLS 3.3.4 software. The relationships among various variables in the model were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). Overall, the study’s findings reveal that Lean and Six Sigma initiatives positively and significantly impact the continuous quality improvement of MSQH-accredited hospitals. The findings also indicate that top management support has a positive and significant relationship with teamwork and vice versa, i.e. teamwork significantly affects Lean and Six Sigma initiatives.